Prevalence, antimicrobial susceptibility profiles and case fatality rates of Acinetobacter Baumannii sepsis in a neonatal unit - Thomas, Reenu; Wadula, Jeannette; Seetharam, Sharona; Velaphi, Sithembiso (The Journal of Infection in Developing Countries, 2018)
Introduction: The burden of sepsis in neonates due to Acinetobacter baumannii (A. baumannii) in developing countries is not well reported. The objective of this study was to determine prevalence of culture confirmed sepsis due to A. baumannii, antimicrobial susceptibility and case-fatality rates (CFR) due to this organism. Methodology: A retrospective review of medical and laboratory records of neonates admitted to a tertiary government hospital from a developing country was conducted. Records of neonates with positive microbiological cultures from blood or cerebrospinal fluid due to A. baumannii were reviewed for demographic characteristics, clinical presentation, laboratory findings, antibiotic susceptibility and outcome at hospital discharge. Results: There were 399 isolates of A. baumannii cultured from sterile sites, with a prevalence of 4.3/1000 live births or 22.8/1000 admissions, accounting for 13% of all culture confirmed sepsis. Majority of neonates were preterm (91%) with a mean gestational age and birth weight of 30 weeks and 1400 grams respectively. Antimicrobial susceptibility of isolates was 64% to cephalosporins, 21% to aminoglycosides and 17% were extremely-drug resistant (XDR), only susceptible to colistin. The CFR was 32%. Factors associated with mortality were presence of a central venous catheter prior to onset of sepsis (49% vs 31%, p = 0.03); need for mechanical ventilation (62% vs 36%, p = 0.005) and inotropic support (57% vs 17%, p < 0.001). Conclusions: A. baumannii is a significant pathogen causing sepsis in neonates, with 17% of them being XDR. It is associated with high CFR. These findings highlight the need for strict enforcement of infection control and antibiotic stewardship practices.